Evaluation of Glycerine from Biodiesel Production as a Feed Ingredient for Broilers - Cerrate, S.; Yan, F.; Wang, Z.; Coto, C.; Sacakli, P.; Waldroup, P.W. (International Journal of Poultry Science, 2006)
Glycerine from biodiesel production was used as a pure energy source in broiler diets formulated to meet typical commercial standards. In the first experiment, glycerine was added at 0, 5, and 10% of the diet while in the second experiment glycerine was added at 0, 2.5, and 5%. Glycerine was assigned a metabolizable energy value of 3527 ME kcal/kg in formulating the diets. In each experiment the various treatments were assigned to eight replicate pens of 60 male broilers each. In the first experiment, birds fed diets with 5% glycerine did not differ significantly in performance from birds fed the control diet with no glycerine. Birds fed diets with 10% glycerine consumed significantly less feed than did those fed diets with 0 or 5% glycerine and consequently had significantly reduced body weight. It is felt that this was due in large part to reduced flow rate in the feeders used in this study as previous researchers have shown acceptance of higher levels of glycerine. In the second study, birds fed diets with 2.5 or 5% glycerine had growth rate and feed conversion that did not differ significantly from that of birds fed the diet with no glycerine. Breast yield as a percent of the dressed carcass was significantly greater for birds fed diets with 2.5 or 5% glycerine as compared to those fed the diet with no glycerine. These data indicate that glycerine from biodiesel can be a useful energy source for use in broiler diets. Concerns remain regarding acceptable levels of residual methanol resulting from separation of the fatty acids in biodiesel production.